A comparison between reduced dimensionality and mixed quantum/classical evaluations of k(T) using the flux-flux correlation function formalism - Clavero, Esteban Dario (2011)
Rate constants for the planar H + HD → H2 + D reaction with J = 0 have been calculated employing reduced dimensionality, mixed quantum/classical and full quantum computations based on the flux-flux correlation function formalism. It has been found that reduced dimensionality and mixed quantum/classical calculations afford quite similar results. This suggests that, for direct reactions occurring in the gas phase, there is no advantage in using the more involved mixed quantum/classical approach. On the other hand, the comparison between approximate and accurate results indicates that both, reduced dimensionality and mixed quantum/classical approaches, work well at medium and high temperatures. As expected, they fail at very low temperatures where tunnelling prevails.